Utilizing Standards in Competency Assessment for General Education – A Case Study of British Columbia, Canada and Lessons for Vietnam - Duong, Thi Thanh Huong; Vu, Truong An (Journal of Education For Sustainable Innovation, 2023)
The utilization of standards in competency assessment is a critical consideration in contemporary education. This study examines the experience of British Columbia in employing standardized criteria for assessing competencies in general education, drawing valuable insights for Vietnam. This paper analyzes the competency assessment frameworks and methods adopted by the province of British Columbia, Canada. It delves into the adoption and adaptation of standards, the alignment of assessment processes with predefined criteria. Findings highlight that incorporating standards in competency assessment enhances assessment validity and transparency. Standards facilitate a more consistent and reliable assessment process, while also aiding the establishment of clear performance expectations for learners. These findings offer valuable lessons for Vietnam's education system, emphasizing the potential benefits and challenges of integrating standardized criteria into competency assessment practices.